Translanguaging como práctica discursiva de brasileiras e brasileiros na Argentina - Da Silva Santana Lopes, Barbara (Cuadernos de la ALFAL.)
With the intention of legitimizing dynamic linguistic practices in which it's possible to observe the fluidity between two or more languages, we propose a view detached from monolingual hegemonic categories in order to enhance effective communication concerning the use of linguistic repertoire of speakers. In our study, we follow the investigations developed by Ofelia Garcia and Ricardo Otheguy (2015) in which they study Brazilians who live in Buenos Aires and Gran Buenos Aires, observing this communicative practice between groups who share the same discursive resources in their construction of meaning. To analyze that, we make use of original material that was collected as part of a Doctorate thesis. In this practice, we can see the emergence of an identity conformed by migrants that constantly negotiate with their own linguistic repertoires in order to optimize their discourse, by which they constitute their self for the other.